Best practice Pengembangan Kompetensi Guru Melalui Kelas Menulis Media Daring - Adi Tama (Program Pascasarjana, Universitas Islam Bunga Bangsa Cirebon, 2021)
The program of Gerakan Literasi Sekolah (GLS), literacy becomes the main capital in growing the culture of literate people. This is not only applying for students as future asset, but also for teachers who meet the disruption era, the accelerating era of the industrial revolution 4.0. Teachers as vital subjects of education must be able to improve their literacy skills. It is proper if the teachers are able to express all ideas and visualizations he thinks in the form of aksara. This best practice research uses a qualitative descriptive method. A good practice program based on real experience carried out in Cirebon as a follow-up to mentoring after the Guru Menulis Workshop. Teachers and principals with total of 120 people, consisting of elementary, middle school and high school teachers gathered in an online group Guru Penulis (WA). Every night the teachers work on writing assignments given by the mentor (tutor). Then the assignments were collected as work savings which will later be made into a book. The results were very satisfying, teachers’ writing motivation grow with smile of enthusiasm to create many independent works as well as an anthology of the teachers’ masterpiece even students in Cirebon, West Java Province. ABSTRAK Dalam program Gerakan Literasi Sekolah (GLS) literasi baca tulis menjadi modal dasar utama dalam menumbuhkan budaya insan literat. Hal ini tidak hanya berlaku bagi siswa sebagai aset masa depan, tetapi juga bagi guru pembelajar dalam menyongsong era disrupsi, era percepatan revolusi industri 4.0. Guru sebagai subjek vital pendidikan harus mampu meningkatkan kemampuan literasinya. Sudah selayaknya jika guru mampu menuangkan segala gagasan, ide, serta visualisasi pikirnya dalam bentuk akasara. Penelitian best practice ini menggunakan metode deskriptif kualitatif. Sebuah program praktik baik berdasarkan pengalaman nyata yang dilakukan di Kota Cirebon sebagai tindak lanjut pendampingan pasca Workshop Guru Menulis. Para guru dan kepala sekolah dengan jumlah 120 orang, yang terdiri dari guru SD, SMP, hingga SMA berkumpul dalam satu grup guru penulis daring (WA). Setiap malam para guru tersebut mengerjakan tugas menulis yang diberikan mentor (guru pembimbing). Selanjutnya tugas demi tugas itu dikumpulkan sebagai tabungan karya yang nantinya akan dijadikan buku. Hasilnya sangat memuaskan, motivasi menulis para guru di Kota Cirebon tumbuh dengan senyum semangat hingga banyak tercipta karya mandiri maupun antologi buah tangan guru pun siswa di Kota Cirebon Provinsi Jawa Barat..